Psychoactive drug and medication use among patients referred to a tertiary sleep laboratory population. (December 2020) - Ogeil, Rowan P.; Prasad, Shivonne; O'Driscoll, Denise M.; Li, William Y.H.; Lubman, Dan I.; Young, Alan C.
Highlights: We investigated the prevalence of commonly used psychoactive drugs (alcohol and caffeine), and medications in a sleep laboratory population, and the relationship between use and sleep and performance outcomes. Caffeine use was ubiquitous, and was associated with a reduction in excessive sleepiness symptomology; high scores on the alcohol use disorders identification test were associated with increased near-miss motor crashes. Polypharmacy was common, with a greater number of medications used associated with poorer sleep quality, and changes in sleep architecture. Our study maps commonly used drugs in those attending a sleep clinic, and demonstrates the association between drug use and sleep outcomes assessed objectively and subjectively. Abstract: Psychoactive drugs including alcohol, caffeine, and prescription medications are commonly consumed to alter sleep/wake states, however the prevalence and impact of these drugs among populations seeking assessment from sleep physicians are unknown. We investigated the prevalence of commonly used drugs (alcohol and caffeine), and medications in a population (N=120; 50 females and 70 males) attending a tertiary sleep clinic for diagnostic polysomnography (PSG) assessment. In addition to objective sleep assessment, participants completed questionnaires assessing sleep quality (Pittsburgh Sleep Quality Index, PSQI), daytime sleepiness (Epworth Sleepiness Scale, ESS), depression and anxiety (Hospital Anxiety and Depression Scale, HADS), alcohol use (Alcohol Use Disorders Identification Test, AUDIT), caffeine and medication use, as well as their experience of adverse events (motor vehicle accidents and near-miss crashes). Caffeine was consumed by 90% of the population and was associated with a reduction in excessive sleepiness symptomology; while high AUDIT scores were associated with increased near-miss crashes. Polypharmacy was common, with a greater number of medications associated with poorer sleep quality, and changes in sleep architecture. This study maps commonly used drugs in those attending a tertiary sleep clinic, and demonstrates associations between drug use and sleep outcomes assessed objectively and subjectively.